A model for designing group task assessments - Olatunji, Oluwole (2016)
This study uses quasi-experimental method to develop a framework for peer assessment in group tasks. A total of 94 students who completed a first year CM undergraduate unit were analysed. The 10 criteria used in the peer assessment framework ensured all students within a group are mutually accountable to their individual commitment to learning in the group. In addition, the framework can be used to predict group success. A Cronbach Alpha’s reliability estimate of 0.968 was obtained when the criteria were tested for internal validity. Principal component and scoring factor analyses were used to elicit the relative importance of each peer assessment criterion: the most significant were ‘Timeliness of contributions’, ‘Reliability of individual’s inputs’, ‘Value of individual’s contributions’ and ‘Individual’s motivation to succeed’; ‘Communication’ is least important item. Correlations between the variables were also obtained. Results showed a strong relationship between peer assessment success and the overall success in the unit i.e. students were able to learn genuinely in their teams and were able to succeed in the unit.